Instagram account @surabaya as a Trusted Source of Information for Surabaya Students - Fitria Febriana Rachman; Didiek Tranggono; Zainal Abidin Achmad (Universitas Islam Balitar, 2021)
This study proves that Surabaya students have high trust in the Instagram account @surabaya as a source of information. The @surabaya account is an official instagran account belonging to the Public Relations of the Surabaya City Government which provides information, entertainment, knowledge, development of education, food and tourism in the city of Surabaya. This study uses the theory of Uses and Gratifications. The classification of motives is used according to McQuail's motive categories: Information Motive, Personal Identity Motive, Integration Motive and Social Interaction, and Entertainment Motive. The research method used is descriptive quantitative. The population of this research is Surabaya students who access the @surabaya account with an age limit of 18-25 years. Determination of sampling in the study using purposive sampling technique, namely taking samples from certain considerations. The results showed that the percentage of the four motives (information, personal identity, integration, and social interaction) was high. This means that Surabaya students consider the Instagram account @surabaya as a reliable source of information about the ins and outs of the city of Surabaya.